Women's Land Army, 1943 (United Kingdom, 1943)
1943 1939-1945 "Women's Land Army, 1943" [HFR0094], 1943 The Women's Land Army was set up to help with harvesting in the First World War and then re-established in June 1939. Women were directed to work in all areas of agriculture and forestry. Adult wages were set at 18 shillings per 50 hours week plus board and lodgings. Membership reached a peak of 87,000 in August 1943, but the Army was not disbanded until 1950.